Agroecological innovation constructing socionatural order for social transformation: two case studies in Brazil - Levidow, Les; Sansolo, Davis [UNESP]; Schiavinatto, Monica [UNESP] (Taylor & Francis, 2021)
The Green Revolution exemplifies the capital-intensive modernization model of resource plunder and labor exploitation. This has provoked small-scale producers and civil society groups to counterpose an agroecology-based solidarity economy (EcoSol-agroecology), especially in Latin America. But their efforts encounter dominant models–of innovation, management, markets, nature, etc.–which limit alternatives. To clarify a transformative agenda, advocates have elaborated agroecological innovation through several complementary practices. Nature is framed as agri-biodiversity complementing socio-cultural diversity. Short food-supply chains (circuitos curtos) build consumer support for production methods enhancing producers' livelihoods, providing socio-economic equity and conserving natural resources. Through diálogos de saberes, i.e. knowledge exchange among farmers and with external experts, cultivation and water-management methods are designed or adapted as socio-environmental technologies. Capacities are built for collective self-management of those solidarity relationships. In such ways, agroecological innovation co-produces specific forms of nature, technoscientific knowledge and society; their practices construct a distinctive socionatural order. Such order arises through several instruments–making identities, institutions and discourses–as understood by STS co-production theory. Here this theory illuminates two Brazilian agroforestry initiatives whose cooperative practices seek to transform their own participants' lives and wider agri-food systems. By combining diverse sources, composite cultures deepen the social basis of territorial belonging.
La innovación agroecológica construyendo el orden socionatural para la transformación social: dos estudios de caso brasileños
Inovação agroecológica construindo ordem socionatural para transformação social: dois estudos de caso brasileiros
Keywords: agroecological innovation; Brazil; socio-environmental technologies; solidarity economy; STS co-production theory